Plasmonic heating from indium nanoparticles on a floating microporous membrane for enhanced solar seawater desalination - Zhang, Lulu (2020)
Passive solar evaporation represents a promising and environmentally benign method of water purification/desalination. Plasmonic nanoparticles have been demonstrated as an effective approach for enhancing solar steam generation through a plasmonic heating effect, nonetheless the efficiency is constrained by unnecessary bulk heating of the entire liquid volume, while the noble metals commonly used are not cost-effective in terms of availability and their sophisticated preparation. Herein, a paper-like plasmonic device consisting of a microporous membrane and indium nanoparticles (In NPs/MPM) is fabricated through a simple thermal evaporation method. Due to the light-weight and porous nature of the device, the broadband light absorption properties, and theoretically the excellent plasmonic heating effect from In NP which could be even higher than gold, silver and aluminium nanoparticles, our device can effectively enhance solar water evaporation by floating on the water surface and its utility has been demonstrated in the solar desalination of a real seawater sample. The durability of the device in solar seawater desalination has also been investigated over multiple cycles with stable performances. This portable device could provide a solution for individuals to do water/seawater purification in under-developed areas with limited/no access to electricity or a centralized drinking water supply.